2020
DOI: 10.1002/ecs2.3050
|View full text |Cite
|
Sign up to set email alerts
|

Ignoring temperature variation leads to underestimation of the temperature sensitivity of plant litter decomposition

Abstract: The majority of terrestrial net primary production decomposes, fueling detrital food webs and converting dead plant carbon to atmospheric CO2. There is considerable interest in determining the sensitivity of this process to climate warming. A common approach has been to use spatial gradients in temperature (i.e., latitude or elevation) to estimate temperature sensitivity. However, these studies typically relate decomposition rates to average temperatures at each site along such gradients, ignoring within‐site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Annual mean temperature showed no relationship to temperature variance (standard deviation of the annual mean) across the nine sites, so we ignored any effect of variance on estimating temperature dependence of litter breakdown (Tomczyk et al. 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Annual mean temperature showed no relationship to temperature variance (standard deviation of the annual mean) across the nine sites, so we ignored any effect of variance on estimating temperature dependence of litter breakdown (Tomczyk et al. 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Hendrick Mill and Little Schultz showed the smallest annual temperature variation, while Raccoon, Choccolocco, and Lick showed the greatest annual variation (Appendix S1: Table S1). Annual mean temperature showed no relationship to temperature variance (standard deviation of the annual mean) across the nine sites, so we ignored any effect of variance on estimating temperature dependence of litter breakdown (Tomczyk et al 2020).…”
Section: Temperature Regimesmentioning
confidence: 99%
“…Under natural conditions, microbial fragmentation, physical abrasion, and consumption by macro-invertebrates can all drive meaningful amounts of leaf breakdown (Marks, 2019;Wilmot et al, 2021). Furthermore, our simulations were conducted at a constant temperature, which would lead to depressed rates of breakdown relative to simulations that include temperature variability (Tomczyk et al, 2020). Not including these processes in our model likely explains the high residence time of leaves in our simulations; at the low nutrient concentration and temperature our simulations had leaf residence times over 1000 d (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Under natural conditions, microbial fragmentation, physical abrasion, and consumption by macroinvertebrates can all drive meaningful amounts of leaf breakdown (Marks, 2019;Wilmot et al, 2021). Furthermore, our simulations were conducted at a constant temperature, which would lead to depressed rates of breakdown relative to simulations that include temperature variability (Tomczyk et al, 2020). Not including these processes in our model likely explains the high residence time of leaves in our simulations; at the low nutrient concentration and temperature our simulations had leaf residence times over 1000 days (Figure 4b), while field studies have found residence times of around two years for Rhododendron leaves in minimally impacted streams (Manning et al, 2015).…”
Section: Discussionmentioning
confidence: 99%